Challenges of the Interdisciplinary Character of Women’s/Gender Studies: Cases of the Czech Republic, Macedonia, and Turkey: Проблемите со интердисциплинарниот карактер на женските/родовите студии: Примерите со Република Чешка, Македонија и Турција - Alkan, Ayten; Milosavljević-Čajetinac, Tijana; Gavritova, Viktorija; Janeva, Kalina (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Ayten Alkan, Tijana Milosavljević-Čajetinac and Viktorija Gavritova | Ајтен Алкан, Тијана Милосављевиќ-Чајетинац и Викторија Гавритова Title (English): Challenges of the Interdisciplinary Character of Women’s/Gender Studies: Cases of the Czech Republic, Macedonia, and Turkey Title (Macedonian): Проблемите со интердисциплинарниот карактер на женските/родовите студии: Примерите со Република Чешка, Македонија и Турција Translated by (English to Macedonian): Kalina Janeva | Калина Јанева Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 11-67 Page Count: 56 Citation (English): Ayten Alkan, Tijana Milosavljević-Čajetinac and Viktorija Gavritova, “Challenges of the Interdisciplinary Character of Women’s/Gender Studies: Cases of the Czech Republic, Macedonia, and Turkey,” Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007): 11-67. Citation (Macedonian): Ајтен Алкан, Тијана Милосављевиќ-Чајетинац и Викторија Гавритова, „Проблемите со интердисциплинарниот карактер на женските/родовите студии: Примерите со Република Чешка, Македонија и Турција“, превод од англиски Калина Јанева, Идентитети: списание за политика, род и култура, т. 6, бр. 1 (зима 2007): 11-67.